2011
DOI: 10.1021/nl200772d
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Antennas for Directional Sorting of Fluorescence Emission

Abstract: Spontaneous emission of fluorescent molecules or quantum dots is radiated along all directions when emitters are diluted in a liquid solution, which severely limits the amount of collected light. Besides, the emission direction does not carry any useful information and cannot be used to sort different molecules. To go beyond these limits, optical antennas have been recently introduced as conceptual tools to control the radiation properties for nanoemitters fixed on a substrate. Despite intense recent research,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
221
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(230 citation statements)
references
References 49 publications
5
221
0
Order By: Relevance
“…Most designs, however, are based on the epi-illumination techniques where the incident pump power and the luminescent radiation share the same half-space. See for example the study undertaken by Aouani et al [10,11] on the fluorescence of an ensemble of molecules with randomly oriented dipole moments, trapped inside a plasmonic aperture, when illuminated and collected through the glass substrate. A more deterministic study showed the dependence of the radiation pattern of plasmonic antennas with respect to the distance and the dipolar orientation of a nearby nano-diamond with NV- [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…Most designs, however, are based on the epi-illumination techniques where the incident pump power and the luminescent radiation share the same half-space. See for example the study undertaken by Aouani et al [10,11] on the fluorescence of an ensemble of molecules with randomly oriented dipole moments, trapped inside a plasmonic aperture, when illuminated and collected through the glass substrate. A more deterministic study showed the dependence of the radiation pattern of plasmonic antennas with respect to the distance and the dipolar orientation of a nearby nano-diamond with NV- [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…[3] These effects result from the strict control over the local density of photon states around the emitter they provide. [4][5][6][7][8] However, the necessary confinement of the active material in a small region close to the metallic resonator entails a restriction on the maximum radiance achievable. An alternative to employing metallic nanostructures is the use of hybrid metal-dielectric systems [9,10] where the electromagnetic field can be tailored in such a way that the emission of light sources can be enhanced while reducing absorption losses.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, structures supporting localized surface plasmon resonances like single metal nanoparticles [2], more complicated nanoparticle structures [3], nanoapertures in metal films [4,5], and diffractive structures [6,7] have proven efficient at redirecting luminescence from single luminophores. In the case of isolated metal nanoparticles, the plasmon resonances provide high local fields close to the particles.…”
Section: Introductionmentioning
confidence: 99%